Analysis of public perception of central banks digital currencies: A survey analysis - Pişkin, Filiz (İstanbul Bilgi Üniversitesi, 2021)
ABSTRACT: Human is the creature that can adapt most easily to all kinds of changes. Along with the technological revolutions experienced around the world, our habits and needs are changing rapidly. “Saving time” is one of the things that humanity needs most today. New approaches emerging both in sociological, economic and scientific dimensions stem from the need for rapid and excessive consumption. In return, it forces you to think fast and produce fast. On the basis of the concept of economy, which is the focus of production and consumption, money and its functions lie. Money, like all other social and economic elements, has begun to evolve with the digital transformation. So, it's time to look ahead and consider what kind of money and payment systems will be needed to meet the needs of the increasingly digital economy. With the transition to Digital Transformation and Digital Economy, paper banknotes, the most common form of money, began to give way to payments with debit cards, virtual POS and QR codes. This evolution in the economy gained different dimensions with the inclusion of the Blockchain Algorithm in payment systems. The use of the Distributed Ledger structure together with the concept of crypto assets has created a new formation such as decentralized digital money, which cannot yet be classified as a type of money. Today, a decentralized payment system contains many uncertainties that are not reliable in terms of the economic policies of the States. Therefore, as a result of the development of the Digital Economy, Central Banks print their Central Bank Digital Money (CBDC) electronically and present them to the public as a new payment system through digital wallets. Some countries create their own CBDC systems, while others try to adapt applied models. Therefore, it is very important to understand the current models in terms of adapting CBDC in the form of National Official Digital Currency. In the literature review, the reasons for many countries taking action regarding CBDCs; The emergence, development and results of the Bahamas Sand Dollar Project, which is accepted as the first official retail CBDC example and officially started to be implemented in 2019, have been seen to be effective. In addition, in the Working Paper published by the Bank of England in 2020, the xiii opportunities and challenges that CBDCs will create when they are implemented in the UK are discussed with their most critical points in terms of the risks they may create in financial markets, society and institutions through the Platform Model. These two models were also taken into account when other countries were creating their transitional designs to CBDC. In the continuation of this study, the studies of the main countries that have made progress on CBDCs in the world are mentioned too and information about the current situation is given. With these inferences from the models, it has been determined that CBDCs have many important advantages such as tax evasion, preventing financial terrorism such as fraud and providing low cost, but they have disadvantages that can negatively affect monetary policy, financial stability and the banking sector if not implemented well. A survey study was conducted on the online platform to measure the public perception of the advantages and disadvantages determined. In this survey study, 3 questions about gender, age and the sectors they work for people who have a financial background and work in the finance sector and those who do not work in the finance sector; A total of 26 questions were asked, 23 of which were Likert scale questions, about the advantages and disadvantages of CBDC. A total of 317 people were reached through the survey. The data collected as a result of the research were evaluated with Cronbach's Alpha and Independent Sample t-Test, and it was observed that people with a financial background were significantly different from those who are not from financial sector, and that the public did not have enough information about CBDCs according to the sample group. So, Central Banks should be very careful when transitioning to Digital Currencies and raise public awareness on this issue.

ÖZET: İnsan her türlü değişime en kolay uyum sağlayabilen varlıktır. Dünyada yaşanan teknolojik devrimlerle birlikte alışkanlıklarımız ve ihtiyaçlarımız da hızla değişiyor. “Zaman tasarrufu” günümüzde, insanlığın en çok ihtiyaç duyduğu şeylerden biridir. Hem sosyolojik hem ekonomik hem de bilimsel boyutta ortaya çıkan yeni yaklaşımlar, hızlı ve aşırı tüketim ihtiyacından kaynaklanmaktadır. Bu yeni yaklaşımlar sizi hızlı düşünmeye ve hızlı üretmeye zorlar. Üretim ve tüketimin odak noktası olan ekonomi kavramının temelinde para ve işlevleri yatmaktadır. Para, diğer tüm sosyal ve ekonomik unsurlar gibi dijital dönüşümle birlikte gelişmeye başlamıştır. Bu sebeple artık geleceğe bakmanın ve giderek artan dijital ekonominin ihtiyaçlarını karşılamak için ne tür para ve ödeme sistemlerine ihtiyaç duyulacağını düşünmenin zamanı geldi. Dijital Dönüşüm ve Dijital Ekonomiye geçiş ile beraber en yaygın para formu olan kâğıt banknotlar yerini banka kartı, sanal pos ve kare kod ile ödemelere bırakmaya başladı. Ekonomideki bu evrim ödeme sistemlerine Blok Zincir Algoritmasının da dahil olmasıyla farklı boyutlar kazandı. Dağıtık Defter yapısının kripto varlık kavramıyla beraber kullanılmaya başlanması merkeziyetsiz dijital para gibi henüz bir para çeşidi olarak sınıflandırılamayan yeni bir oluşumu meydana getirdi. Günümüzde merkeziyetsiz bir ödeme sistemi, devletlerin ekonomi politikaları açısından güven taşımayan birçok belirsizliği barındırır. Dolayısıyla Dijital Ekonominin gelişmesi sonucunda Merkez Bankaları, Merkez Bankası Dijital Paralarını (MBDP) elektronik ortamda basmakta ve dijital cüzdanlar aracılığıyla yeni bir ödeme sistemi olarak kamuoyuna sunmaktadır. Bazı ülkeler kendi MBDP sistemlerini yaratırken bazıları ise uygulanmış modelleri uyarlamaya çalışmaktadır. Bu nedenle MBDP’lerin, Ulusal Resmi Dijital Para formunda uyarlanabilmesi açısından mevcut modelleri kavramak çok önemli bilgi kaynaklarıdır. Literatür taramalarında, birçok ülkenin MBDP’ler ile ilgili aksiyon almasında; ilk resmi perakende MBDP örneği olarak kabul edilen ve 2019 yılında resmen uygulanmaya başlamış Bahamalar Kum Doları Projesi’nin ortaya çıkışının, gelişiminin ve yarattığı sonuçların etkili olduğu görülmüştür. Bununla beraber 2020 yılında İngiltere Merkez Bankası tarafından yayınlanan Çalışma Tebliği’nde MBDP’lerin, Birleşik Krallık’da uygulanmaya gireceği zaman yaratacağı fırsat ve zorluklar, Platform Model üzerinden finansal piyasalarda, kurumlarda ve toplumlarda yaratabileceği riskleri bakımından, en kritik noktalarıyla tartışılmıştır. Bu iki modelin, diğer ülkeler tarafından da MBDP’ye geçiş tasarımlarını oluştururken dikkate alındığı görülmüştür. Bu çalışmanın devamında dünyada MBDP'ler konusunda ilerleme kaydeden başlıca ülkelerin çalışmalarından da bahsedilmiş ve mevcut durum hakkında bilgi verilmiştir. Modellerden elde edilen bu çıkarımlar ile MBDP’lerin vergi kaçırma, sahtecilik gibi finansal terörü önleme ve düşük maliyet sağlama gibi birçok önemli avantajı barındırdığı fakat iyi uygulanmadığı takdirde para politikasını, finansal istikrarı ve bankacılık sektörünü olumsuz etkileyebilecek dezavantajları olduğu belirlenmiştir. Belirlenen avantaj ve dezavantajlara ilişkin kamuoyu algısını ölçmek için online platform üzerinden bir anket çalışması yapılmıştır. Bu anket çalışmasında finansal bilgi geçmişine sahip olan ve finans sektöründe çalışan kişiler ile finans sektöründe çalışmayan kişilere cinsiyet, yaş ve bulundukları sektörler hakkında 3 adet; MBDP’nin avantajları ve dezavantajları hakkında da 23 adet Likert ölçekli soru olmak üzere toplam 26 adet soru sorulmuştur. Anket ile toplam 317 kişiye ulaşılmıştır. Araştırma sonucunda toplanan veriler, Cronbach’s Alfa ve Bağımsız Örneklem t-Test ile değerlendirilmiş, neticede finansal geçmişe sahip olan kişilerin, finans sektöründen olmayan kişilerden anlamlı derecede farklı olduğu ve örneklem grubuna göre kamuoyunun MBDP’ler hakkında yeterli bilgiye sahip olmadığı gözlemlenmiştir. Bu nedenle Merkez Bankaları, Dijital Paralara geçiş yaparken çok dikkatli davranmalı ve halkı bu konuda bilinçlendirmelidir.
Merkez bankaları dijital para birimlerine ilişkin kamu algısının analizi: Anket analizi
Keywords: Merkez Bankası Dijital Parası; Kripto Varlık; Finansal İstikrar; Dağıtık Defter Yapısı; Blok Zincir; Central Bank Digital Money; Crypto Asset; Financial Stability; Distributed Ledger Structure; Blokchain